Africa, a study in tropical development - Stamp, L. Dudley (New York : John Wiley & Sons, 1953)
The author in this book aims to look at the continent of Africa: to consider its geographical background as an environment for human activity and to study the responses which have been evoked from its African inhabitants and those who, in the last few centuries, have penetrated its fastnesses and molded its fortunes. The book is divided into three parts: The African Continent; The Countries and Regions of Africa and Africa Today.
Includes bibliographical references and index.
aia 16/11/2017
Loans
Keywords: Physical geography -- Africa; Africa -- Economic conditions; Africa -- Description and travel; Travel; Africa